Antimycobacterial Activity of Constituents from Foeniculum vulgare Var. Dulce Grown in Mexico - Esquivel Ferriño, Patricia Cristina; Favela Hernández, Juan Manuel de Jesús; Garza González, Elvira; Waksman Minsky, Noemí Herminia; Ríos, María Yolanda; Camacho Corona, María del Rayo (2012)
Bioassay guided fractionation of an antimycobacterial extract of Foeniculum vulgare var dulce (Apiaceae) led to the isolation and characterization of 5-hydroxyfuranocoumarin. The chemical structure of this compound was elucidated by 1 H and 13C (1D and 2D) Nuclear Magnetic Resonance (NMR) spectroscopy. In addition, the active fractions were analyzed by GC-MS and seventy eight compounds were identified; the major compounds were 1,3-benzenediol, 1-methoxycyclohexene, o-cymene, sorbic acid, 2-hydroxy-3-methyl-2-cyclopenten-1-one, estragole, limonene-10-ol and 3-methyl-2- cyclopenten-1-one. Twenty compounds identified in the active fractions were tested against one sensitive and three MDR strains of Mycobacterium tuberculosis using the Alamar Blue microassay. Compounds that showed some degree of antimycobacterial activity against all strains tested were the following: linoleic acid (MIC 100 µg/mL), oleic acid (MIC 100 µg/mL), 1,3-benzenediol (MIC 100–200 µg/mL), undecanal (MIC 50–200 µg/mL), and 2,4-undecadienal (MIC 25–50 µg/mL), the last being the most active compound. To our knowledge, this is the first report of the presence of 5-hydroxyfuranocoumarin in F. vulgare.